The Application of Risk Management as A Predictor of Performance Planning Quality at the Ministry of Home Affairs - Nadya Nastiti; Henryanto Wijaya (Jurnal Indonesia Sosial Sains, 2026)
This research aims to analyze the implementation of risk management as a predictor of performance planning quality at the Ministry of Home Affairs. The study is motivated by the low Risk Management Index (RMI) score within the Ministry, which indicates that risk management implementation has not yet run effectively and has not been consistently integrated into organizational management processes. The paradox between the low Risk Management Index (RMI) and the relatively high performance planning score at the Ministry of Home Affairs reveals a gap between the normative condition that requires the integration of risk management into performance planning and the empirical reality observed in the field, a condition worthy of further examination. This research employs a quantitative explanatory approach, with purposive sampling used to select 66 Civil Servants (Aparatur Sipil Negara/ASN) who are directly involved in performance planning and/or risk management processes within the Ministry of Home Affairs. The findings indicate that risk management implementation at the Ministry of Home Affairs has not yet been fully integrated into organizational management processes. On the other hand, the quality of performance planning is perceived to be relatively good based on the perceptions of civil servants. The study reveals a paradox between the low Risk Management Index (RMI) score and the high achievement of the Government Agency Performance Accountability System (AKIP).